Allocation of risk in the oil and gas contracts in Malaysia: An empirical study - Wan Zahari, Wan Mohd Zulhafiz (Society of Interdisciplinary Business Research (SIBR), 2017)
Oil and gas projects are risky undertakings, which may cause severe damage to property and the environment, not to mention, personal injury and death to personnel. Contractual provision such as an indemnity and mutual hold harmless clause is used as a tool in allocating the risks. However, as a consequence of the private and government litigation arising from the Macondo oil spill in the Gulf of Mexico in 2010 as well as revised perceptions of risk exposure, evidence suggests that operators generally are seeking to modify the established approach to liability allocation through individual contract negotiations with contractors. This scenario has significant and potentially adverse financial implications for the contractors and for the long-term sustainability of the industry. In this respect, there is a tendency that the oil companies will pass a greater share of the risks onto contractors. This problem could lead to financial impairment and unfairness to the contractors. An empirical study was conducted to investigate the issues and problems with regard to risk allocation provisions and indemnity and hold harmless clauses of oilfield service contracts in Malaysia. The data for the empirical study was drawn from the intensive semi-structured interviews of ten respondents from oil companies, contractors and one legal practitioner. The finding of this empirical study indicates that contractors are concerned about the one-way adversarial style of operator-contractor relationship and also that they are being allocated more contractual risks. The methodology employed in this paper will essentially be a combination of literature review and qualitative study i.e. semi-structured interview, which will be carried out in a prescriptive, comparative and analytic manner.